Treatment efficacy of repositioning maneuvers in multiple canal benign paroxysmal positional vertigo: a systematic review and meta-analysis - Alfarghal, Mohamad; Singh, Niraj Kumar; Algarni, Mohammed Abdullah; Jagadish, Nirmala; Raveendran, Rajesh Kumar (Frontiers in Neurology, 2023)
Introduction Benign paroxysmal positional vertigo (BPPV) involving the posterior canal is more common than other canals; however, simultaneous involvement of multiple canals can be seen up to 20% of all BPPV cases. The diagnosis and management of multiple canal BPPV can be quite challenging due to the complexity of findings. Therefore, this systematic review and meta-analysis aimed at unveiling the most effective repositioning strategy for the treatment of multiple canal BPPV. Methods A literature search through PubMed, Scopus, and Web of Science databases was conducted using search terms such as BPPV, multiple canals, bilateral BPPV, repositioning maneuvers etc. After duplicate removal, the retained articles underwent various stages of elimination by two independent reviewers, and a third reviewer resolved the discrepancy between them. Results A total of 22 articles were included in the systematic review. These publications documented 5,196 patients diagnosed with BPPV, of which 513 had multiple canal BPPV. Of 295 individuals with multiple canal BPPV, 58.9% were effectively treated in 1 session, whereas 18.3 and 4.4% achieved a symptom-free state after two and three sessions, respectively. Failure of treatment using repositioning maneuvers was found in 18.4%. Possible implications This study offers insight into the real world of BPPV management in single and multiple canal BPPV. It is evident that repositioning maneuvers provide rapid and long-lasting relief of BPPV in most single canal BPPV patients; however, multiple canal BPPV often requires repeated treatment, and the risk of recurrence is higher in this variety than the single canal BPPV.